2019
DOI: 10.1111/cpr.12711
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of lysine‐specific demethylase 1A suppresses neointimal hyperplasia by targeting bone morphogenetic protein 2 and mediating vascular smooth muscle cell phenotype

Abstract: Objectives: Vascular disorders are associated with phenotypical switching of vascular smooth muscle cells (VSMCs). We investigated the effect of bone morphogenetic protein (BMP)-2 in controlling VSMC phenotype and vascular disorder progression.Lysine (K)-specific demethylase 1A (KDM1A) has been identified to target BMP-2 and is employed as a therapeutic means of regulating BMP-2 expression in VSMCs. Materials and methods:VSMCs were stimulated with angiotensin II, and the expression of KDM1A and BMP-2 was detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…The transition from the contractile to the synthetic phenotype causes abnormal VSMC proliferation [ 1 ]. Therefore, we evaluated the effects of Daxx on AngII–induced VSMC proliferation and migration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The transition from the contractile to the synthetic phenotype causes abnormal VSMC proliferation [ 1 ]. Therefore, we evaluated the effects of Daxx on AngII–induced VSMC proliferation and migration.…”
Section: Resultsmentioning
confidence: 99%
“…Upon infliction of vascular injury, VSMCs proliferate abnormally, migrate, and thicken blood vessel walls. Eventually, they play detrimental roles in the development of cardiovascular diseases such as atherosclerosis and intimal hyperplasia [ 1 , 2 ]. Therefore, inhibition of the VSMC phenotype switching positively affects cardiovascular disease pathophysiology [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning that dysfunctional endothelial cells (ECs) and vascular smooth muscle cells (VSMCs) are instrumental in the process of atheroma formation. Interestingly, pharmacological inhibition of LSD1 reduced EC proliferation and inflammatory response, VSMC proliferation, and neointimal hyperplasia [ 59 , 60 , 61 ]. Together, these data suggest that LSD1-related signaling pathways could regulate important pathological aspects in multiple cell types implicated in atherogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The proliferation, migration, and phenotypic switching from contractile to synthetic phenotypes of vascular smooth muscle cells (VSMCs) are critical for neointima formation and vascular restenosis [ 5 ]. Recently, histone methylation was reported to participate in vascular biology, including neointima formation [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…JMJD demethylases catalyze α-ketoglutarate (αKG), oxygen, and Fe(II) to produce succinate and CO 2 in the hydroxylation reaction, in which unstable hemiaminal products are produced and broken into formaldehyde and a demethylated histone product [ 11 , 12 ]. Recently, demethylase KDM3a was reported to be upregulated during neointimal hyperplasia after vascular injury in diabetic rats [ 13 ], and demethylase JMJD3 (KDM6B) and KDM1A were found to be highly expressed in a rat carotid artery balloon injury model [ 5 , 13 ]. These results indicated that KDMs might be involved in neointima formation.…”
Section: Introductionmentioning
confidence: 99%